Fast Extraction and Detection of 4-Methylimidazole in Soy Sauce Using Magnetic Molecularly Imprinted Polymer by HPLC - Zufei Feng (Molecules, 2017)
On the basis of magnetic molecularly imprinted polymer (MMIP) solid-phase extraction coupled with high performance liquid chromatography, we established a new method for the determination of the 4-methylimidazole (4-MEI) in soy sauce. Scanning electron microscopy (SEM), Fourier transform infrared (FT-IR), X-ray diffraction (XRD) and vibrating sample magnetometer (VSM) were used to characterize the synthesized MMIPs. To evaluate the polymers, batch rebinding experiments were carried out. The binding strength and capacity were determined from the derived Freundlich isotherm (FI) equation. The selective recognition capability of MMIPs was investigated with a reference compound and a structurally similar compound. As a selective pre-concentration sorbents for 4-methylimidazole in soy sauce, the MMIPs showed a satisfied recoveries rate of spiked samples, ranged from 97% to 105%. As a result, the prepared MMIPs could be applied to selectively pre-concentrate and determine 4-methylimidazole in soy sauce samples.